The Cardiac Autonomic Response Recovery to the Modified Tilt Test in Children Post Moderate–Severe Traumatic Brain Injury. (3rd July 2022) - Sorek, Gilad; Gagnon, Isabelle; Schneider, Kathryn; Chevignard, Mathilde; Stern, Nurit; Fadida, Yahaloma; Kalderon, Liran; Shaklai, Sharon; Katz-Leurer, Michal
ABSTRACT: Objective: To assess the recovery of the cardiac autonomic control system (CACS) response to the modified tilt-test during rehabilitation, in children post moderate-severe TBI at the subacute phase post-injury. Method: Thirty-seven children aged 6-18 years, 14-162 days post moderate-severe TBI, participated in the study. The assessment included CACS values evaluation (heart rate (HR), heart rate variability (HRV) and blood pressure) during the modified tilt-test: five minutes lying supine and five minutes passive standing. Re-assessment was performed after eight weeks of rehabilitation. Results: In both assessments, only four children reported symptoms associated with orthostatic intolerance during the modified tilt-test. No change was found over time in the HR and HRV values at rest. In response to the modified tilt-test, the systolic blood pressure showed change over time, with a significant interaction effect (p=0.04); while in the first assessment the SBP values showed a hypertension trend in the second assessment the SBP values showed a hypotension trend. Conclusions: Children post moderate-severe TBI at the sub-acute phase post-injury, have a better systolic blood pressure response during the modified tilt-test after eight weeks of individually tailored rehabilitation program, despite no change in the CACS values at rest. Clinical trial gov. number: NCT03215082